Discussion of "Systemic Risk and the Solvency-Liquidity Nexus of Banks" - Tobias Adrian (Federal Reserve Bank of New York, 2015)
Pierret (2015) presents empirical analysis of the solvency-liquidity nexus for the banking system, documenting that a shock to the level of banks' solvency risk is followed by lower short-term debt. Conversely, higher short-term debt Granger-causes higher solvency risk. These results point toward a tight interaction between solvency and liquidity risk over time. My comments are threefold. First, I suggest improving the identification of shocks in Pierret's vector autoregressive setup. Second, I caution against using the quantitative results as the basis for setting policy. Third, I recommend using theoretical restrictions from macro-finance theories to improve identification and interpretation.
Keywords: G01; G21; G28; 330; systemic risk; banking liquidity; capital regulation; liquidity regulation